2016
DOI: 10.4193/rhin15.177
|View full text |Cite
|
Sign up to set email alerts
|

The effect of periorbital cooling on pain, edema and ecchymosis after rhinoplasty: a randomized, controlled, observer-blinded study

Abstract: Cooling of the periorbital region reduces edema and ecchymosis as well as pain; however 3 days of use is enough after rhinoplasty. One hour after surgery, cooling does not affect the pain but reduce edema and ecchymosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Shin et al 5 found that edema increased until the 2 nd postoperative day in the cold application group and until the 3 rd postoperative day in the control group. In our study, however, edema increased until the Also, similar to our study, in few studies with different patient groups, it was found that cold application significantly reduced periorbital edema and ecchymosis scores 7,13 .…”
Section: Effect Of Cold Applicationsupporting
confidence: 89%
See 2 more Smart Citations
“…Shin et al 5 found that edema increased until the 2 nd postoperative day in the cold application group and until the 3 rd postoperative day in the control group. In our study, however, edema increased until the Also, similar to our study, in few studies with different patient groups, it was found that cold application significantly reduced periorbital edema and ecchymosis scores 7,13 .…”
Section: Effect Of Cold Applicationsupporting
confidence: 89%
“…Among those studies evaluating the effect of cold application on periorbital edema and ecchymosis 5,7,13 , only one study 5 provided information about the decrease in periorbital skin temperature after cold application, but none reported the temperature of the tool used in cold application. Therefore, this study provides evidence that cold application with gel packs can be applied to the periorbital area with an average temperature of -14 ºC for 20 minutes each hour without causing any complications.…”
Section: Change Of Skin Temperature After Cold Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…All 48 participants completed the study. Procedures undertaken were FESS [29], septoplasty and cold-steel turbinoplasty as one procedure [13], septoplasty alone [3], cold-steel turbinoplasty alone [2] and bilateral SPA ligation (which involved a middle meatal antrostomy as part of the approach) [1]. None of the patients needed rescue analgesia.…”
Section: Resultsmentioning
confidence: 99%
“…To date, randomised control trials studying similar techniques have produced conflicting results regarding the effect of preemptive anaesthesia on postoperative pain (3,11,12) . Postoperative pain was also a subject of other study which showed positive effect of cold application following septorhinoplasty on reduction of pain scores (13) . However, there is no article in the literature describing the effect of transoral injection of SPG in combination with AEN block.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%